"The Black Swan” in the Supply Chain – From Disruption to Resilience - Agnieszka BUKOWSKA-PIESTRZYNSKA; Jakub DONSKI-LESIUK (Communications of International Proceedings, 2021)
The article presents the concept of a black swan event and its impact on the disruptions of the supply chain operation in the context of covid-19 epidemic. The purpose of the article is to indicate any actions to be taken to make the modern supply chains resilient to the influence of other black swans that may occur in the future. Thus, the concepts of the supply chain and its embedded relational risk have been defined. The determinants of the supply chain resilience and stages of its implementation as well as the multifaceted benefits that result from this resilience have also been identified. Theoretical of nature, the article is based on the literature review.
Keywords: The black swan incident; disruptions in the economy; risk; supply chain; resilient supply chain; supply chain visibility